Senam Ostheoporosis dan Relaksasi Nafas untuk Mencegah Ostheoporosis dan Nyeri Sendi Pada Usia Lansia - Lailaturohmah Kurniawati; Rifani Rahmalia Nugraha; Salsabilla Az Zahra; Salsabillah Naqwa Anom Sari; Siska Dea Saputri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Ostheoporosis is a systemic bone disease characterized by a decrease in bone microarchitecture so that bones become brittle and break easily.The purpose of this outreach is specifically to increase awareness among the elderly about the importance of maintaining bone health, apart from that, it also increases knowledge that osteoporosis can be prevented in various ways and by reducing the pain that arises. The method for the presentation of material about the elderly and ostheoporosis accompanied by the practice of osteoporosis exercises with midwives and the elderly in Pucangan Baru II Village, Rt02/Rw07, Pucangan, Kartasura, Sukoharjo. The results of the counseling in Pucangan Baru II Village, Rt02/Rw07, Pucangan, Kartasura, Sukoharjo showed extraordinary participation, marked by the elderly/audience being very enthusiastic about taking part in Osteoporosis exercises and the audience also felt comfortable when learning the Breathing Relaxation Method provided.